The extent of B‐cell activation and dysfunction preceding lymphoma development in HIV‐positive people1. Issue 2 (31st August 2017) - Shepherd, L; Borges, ÁH; Harvey, R; Bower, M; Grulich, A; Silverberg, M; Weber, J; Ristola, M; Viard, J‐P; Bogner, JR; Gargalianos‐Kakolyris, P; Mussini, C; et al.
Abstract : Objectives: B‐cell dysfunction and activation are thought to contribute to lymphoma development in HIV‐positive people; however, the mechanisms are not well understood. We investigated levels of several markers of B‐cell dysfunction [free light chain (FLC)‐ κ, FLC‐ λ, immunoglobulin G (IgG), IgA, IgM and IgD] prior to lymphoma diagnosis in HIV‐positive people. Methods: A nested matched case–control study was carried out within the EuroSIDA cohort, including 73 HIV‐positive people with lymphoma and 143 HIV‐positive lymphoma‐free controls. Markers of B‐cell dysfunction were measured in prospectively stored serial plasma samples collected before the diagnosis of lymphoma (or selection date in controls). Marker levels ≤ 2 and > 2 years prior to diagnosis were investigated. Results: Two‐fold higher levels of FLC‐ κ [odds ratio (OR) 1.84; 95% confidence interval (CI) 1.19, 2.84], FLC‐ λ (OR 2.15; 95% CI 1.34, 3.46), IgG (OR 3.05; 95% CI 1.41, 6.59) and IgM (OR 1.46; 95% CI 1.01, 2.11) were associated with increased risk of lymphoma > 2 years prior to diagnosis, but not ≤ 2 years prior. Despite significant associations > 2 years prior to diagnosis, the predictive accuracy of each marker was poor, with FLC‐ λ emerging as the strongest candidate with a c‐statistic of 0.67 (95% CI 0.58, 0.76). Conclusions: FLC‐ κ, FLC‐ λ and IgG levels were higher > 2 years before lymphoma diagnosis, suggesting that B‐cell dysfunction occurs many years prior to lymphoma development. However, the predictive value of each marker was low and they are unlikely candidates for risk assessment for targeted intervention.